2020
DOI: 10.1111/jar.12815
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness and people with intellectual disabilities: A systematic review of the international research evidence

Abstract: Background People with intellectual disabilities can experience homelessness, and some of the reasons differ from the general homeless population. Specific policy and practice responses are required. Method A systematic review of studies examining homelessness among people with intellectual disabilities utilizing CINAHL, MEDLINE, PsycINFO and Sociological Abstracts databases from inception to November 2019. Results The search produced 259 papers, and following screening, a total of 13 papers were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…In addition to the high rate of suicide attempts, 100% of the interviewees suffered several physical and psychological ailments, from malnutrition, anemia, HIV, cancer, disability, sclerosis, or fibromyalgia to compulsive disorders, manic depression, and suicidal tendencies. There not only exists a relationship between homelessness and mental disorders [ 49 ], but we have also observed that the more time the homeless individual spends on the streets, the greater the degree of his or her decline in health, well-being, and basic skills [ 28 ] (p. 122). Thus, creating social bonds is often considered a secondary priority after meeting urgent needs in terms of health, shelter, and food.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the high rate of suicide attempts, 100% of the interviewees suffered several physical and psychological ailments, from malnutrition, anemia, HIV, cancer, disability, sclerosis, or fibromyalgia to compulsive disorders, manic depression, and suicidal tendencies. There not only exists a relationship between homelessness and mental disorders [ 49 ], but we have also observed that the more time the homeless individual spends on the streets, the greater the degree of his or her decline in health, well-being, and basic skills [ 28 ] (p. 122). Thus, creating social bonds is often considered a secondary priority after meeting urgent needs in terms of health, shelter, and food.…”
Section: Discussionmentioning
confidence: 99%
“…For example, inequalities in oral health experienced by homeless persons, incarcerated persons and sex workers are often described solely within the social environment, despite the high prevalence of mental health disorders, substance misuse disorders, hepatitis, tuberculosis, cardiovascular and respiratory diseases within these populations 6 . The prevalence of physical and cognitive impairment is extremely high in homeless populations 6–8 (37% and 42%, respectively, in one Irish study 9 ). People with intellectual disability are largely over‐represented in prison populations 10 …”
Section: Conceptualizing the Relationship Between The Social Environm...mentioning
confidence: 99%
“…Inclusion Health is an emergent approach that aims to address extreme health inequalities for populations on the ‘cliff‐edge’ 9,38 . This approach should include the disabled population as a socially excluded group and identify disabled people hidden within other marginalized groups with high prevalence of physical, cognitive and mental impairment 6–9 . There are many ways in which the disability and inequalities in oral health agendas overlap, but for the purposes of this article, four main pathways will be briefly evoked—reducing barriers to access to services; ensuring quality of care; improving oral health promotion and disease prevention; and research and policy recommendations.…”
Section: Building a Common Agendamentioning
confidence: 99%
“…Commissioners require information about the issues that people face, including the role of trauma, and high-quality evidence about effective practice (Moreton et al , 2021). Psychologists and other professionals can contribute to this, as well as understanding of the over-representation in homelessness services of those with brain injury (Groundswell, 2018), autism (The Westminster Homelessness and Health Coordination Project, 2020) and learning disabilities (Brown and McCann, 2021). But those with “professional” psychological awareness must be humble, acknowledge the limitations of existing models in addressing SMD and strive towards developing more adequate theories.…”
Section: Humble Pie: This Is Just the Beginningmentioning
confidence: 99%